Tales from a not-so-smart Miss Know-It-All - Russell, Rachel Renée (Russell, Rachel Renée. Dork diaries, 2012)
When Miss Know-It-All's inbox overflows with pleas for guidance, Nikki Maxwell, the school newspaper advice columnist, turns to her best friends for help.